2010
DOI: 10.3109/02841850903485763
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of 18F-2-deoxy-fluoro-D-glucose positron emission tomography for pn2 lymph nodes in patients with lung cancer

Abstract: Diagnostic accuracy of FDG-PET (47%) was low and similar to that of CT (42%). The possibility of false-negative as well as false-positive findings should be recognized in interpreting PET images. Micrometastasis appeared to be the greatest cause of false-negative findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Similar difficulties are encountered with PET on this issue. Consequently, recent studies [27,28] revealed that the diagnostic accuracy of FDG-PET in diagnosing preoperative nodal status in patients with lung cancer was low and similar to that of CT and underscored the continued need for surgical staging. Apart from this, the definition of lymph node enlargement in clinical practice has not yet been standardised.…”
Section: Discussionmentioning
confidence: 96%
“…Similar difficulties are encountered with PET on this issue. Consequently, recent studies [27,28] revealed that the diagnostic accuracy of FDG-PET in diagnosing preoperative nodal status in patients with lung cancer was low and similar to that of CT and underscored the continued need for surgical staging. Apart from this, the definition of lymph node enlargement in clinical practice has not yet been standardised.…”
Section: Discussionmentioning
confidence: 96%
“…However, most research data have supported systemic MLN dissection as a better choice for two main reasons. Firstly, preoperative noninvasive examinations, such as enhanced CT or positron emission tomography-computed tomography (PET-CT), display poor specificity in judging MLN metastasis, which is associated with certain ratio of cN0-pN2 phenomenon (13,14). Secondly, it can promote a more rigorous outcome of postoperative TNM staging, so as to instruct whether further therapy such as chemotherapy should be given to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nomori et al 4) reported that the size of metastatic foci within lymph nodes was 0.5-9 mm for false-negative cases and 4-8 mm for true-positive cases, and there was a significant difference between these two groups. Additionally, Ozawa et al 8) analyzed PET/CT false-negative lymph nodes in more detail, and they also concluded that the overall size of PET/CT false-negative mediastinal nodes was significantly smaller than that of true-positive nodes (39.3 ± 30.5 mm 2 vs. 106.2 ± 60.1 mm 2 ; p <0.0001). Although these reports were generally consistent with our results, there was few description of the association between histological features of the primary tumor and patterns of lymph node metastasis in these literatures and others.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Some of them evaluated histological findings of metastatic lymph nodes in detail, and they investigated causative factors for false-negative PET scans. However, to our knowledge, few studies have investigated the association between PET false-negative, unexpectedly proven lymph node metastasis and the histological features of primary tumors.…”
Section: Introductionmentioning
confidence: 99%